Equivalence of freeze-dried and liquid-frozen formulations of MVA-BN as smallpox and mpox vaccine - Richard N. Greenberg; Darja Schmidt; Daniela Reichhardt; Siegfried Roesch; Sanja Vidojkovic; Jane Maclennan; Liddy M. Chen; Robert Gruenert; Christian Kreusel; Heinz Weidenthaler; Thomas P.H. Meyer; Paul John Chaplin (Human Vaccines & Immunotherapeutics)
Modified Vaccinia Ankara Bavarian Nordic (MVA-BN) as a smallpox and mpox vaccine has been approved in its liquid-frozen (LF) formulation in the US, Canada, and EU. A freeze-dried (FD) formulation may offer additional benefits, such as a longer shelf life and reduced dependence on cold chain storage and transport. In a phase 2 clinical trial, 651 vaccinia-naïve participants were vaccinated with two doses of MVA-BN LF or FD, 4 weeks apart. The objectives were to compare MVA-BN FD with LF in terms of vaccine-induced immune responses, safety, and reactogenicity. Non-inferiority of the immune response was assessed by the 95% CI of the geometric mean ratios. Both formulations induced robust vaccinia-specific humoral and cellular immune responses. At peak humoral responses (Week 6), geometric means of total antibody titers were 1096 (95% CI 1013, 1186) from the FD group and 877 (95% CI 804, 956) from the LF group, achieving the primary endpoint of non-inferiority of MVA-BN FD compared to MVA-BN LF. At peak cellular responses (Week 2), geometric means of T cell spot forming units were 449 (95% CI 341, 590) from the FD group and 316 (95% CI 234, 427) from the LF group. Both formulations of MVA-BN were well tolerated, with similar unsolicited AEs and solicited systemic reactions in both groups but slightly more local reactions in the FD group. No vaccine-related serious adverse events (SAEs) or vaccine-related AE of special interest were reported. The FD formulation of MVA-BN was shown to be equivalent to MVA-BN LF.